"Se eu morrer nasce outro igual a mim""/If i die, someone will be born like me" - Ricardo de Castro e Silva; Maria Teresa de Arruda Campos (Universidade Estadual de Campinas, 2006)
Este artigo apresenta alguns aspectos da interferência que a psicanálise exerceu no percurso profissional dos autores, que se serviram da dúvida e da busca por outras formas de atuar nas poucas possibilidades que o processo educativo, seja na educação formal (escola) ou na educação não formal (ONG) podia oferecer. Aproximar-se da psicanálise foi uma possibilidade que fez a diferença neste percurso, contribuindo para abrir algumas brechas para que profissionais, alunos, adolescentes e jovens, imersos nesta civilização, pudessem, exercitar o cuidado de si e do outro numa dialética constitutiva da subjetivação de todos. This paper aims at presenting some interfering aspects that the psychoanalysis had on the professional performance of the authors. They took advantage from the doubt and the search for other performing forms in the few possibilities that the educative process could offer, considering either the formal education (the school) or the non-formal one (NGO). Getting closer to the psychoanalysis was a possibility that made the difference in this performance, contributing to open some opportunities, so that professionals like students, teenagers and the youth, immersed in this civilization, could perform the care on themselves and on the other, according to a constituent dialectic from the subjectivation of all.